Dynamics and Stability of Individual Base Pairs in Two Homologous RNA-DNA Hybrids - Huang, Yuegao (2009)
Nuclear magnetic resonance spectroscopy and proton exchange have been used to characterize two RNA-DNA hybrids from the tR2 intrinsic transcription terminator site of phage λ. The hybrids have the same base sequence: 5’-GGCGCAGGCC(T/U)(T/U)CC-3’/5’-GGAAGGCC(T/U)GCGCC-3’, but differ from each other by an interchange of DNA and RNA strands. The opening of single base pairs in the two hybrids is characterized by measuring the rates of exchange of imino protons with solvent protons as a function of the concentration of a proton acceptor (ammonia base) at 10 °C. The free energy change in the opening reaction provides a measure of the stability of the base pair, while the rates of opening and closing define the base-pair dynamics. The results demonstrate that, within the same base sequence context, dA-rU base pairs are less stable than dT-rA base pairs. The differences in stability are enhanced when two dA-rU base pairs are located next to each other in the hybrid structure. For the G-C base pairs, the rates of opening and closing, and the stability are affected by the base sequence context and by the nature of the sugar moiety attached to the guanine. The dominant feature of the base sequence is the proximity of the dA-rU base pair, which destabilizes the G-C base pair when the guanine is located on the DNA strand. Two G-C base pairs (namely, those in the 4(th) and 10(th) positions) exhibit large differences in their opening and closing rates between the two hybrids, while maintaining the same stability. These results provide the first demonstration that, for RNA-DNA hybrid structures with the same base sequence, the opening dynamics and the stability of individual base pairs is strongly influenced by the chemical nature of each strand.